Hubungan Karakteristik dengan Pendapatan Peternak pada Kelompok Ternak Sapi Potong Marga Mukti I di Kecamatan Majalengka - Yuisdisantari, Afrilia; Widianingrum, Dini; Indah Laela Rahmah, ulfa (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
Research on the relationship between breeder characteristics and income in the Marga Mukti I beef cattle breeder comunity in Majalengka District was carried out from September to October 2023. The aim of this research was to determine breeder characteristics and their relationship with breeder business income. The research was conducted through a survey to 55 breeders. The data analysis used is descriptive analysis and spearman correlation. The variable measured is the relationship between breeder characteristics and income. The research results show that the average income of breeders is IDR. 27,282,029/year. The results show that the relationship between breeder characteristics and income is positively correlated, namely breeder age, breeder experience, business scale, and breeder occupation. Meanwhile, the breeder's final education is inversely related to income or can be said to be negatively correlated. It can be concluded that all breeder characteristics have a positive relationship with farmer income levels except the final education level.